2022
DOI: 10.1177/10634266221099242
|View full text |Cite
|
Sign up to set email alerts
|

Special Educator Burnout and Fidelity in Implementing Behavior Support Plans: A Call to Action

Abstract: Special education teachers have one of the most challenging and stressful jobs in public education, which often leads to increased burnout. High levels of burnout have, in turn, been related to lower levels of fidelity of implementation in delivery of evidence-based behavior interventions. The purpose of this position paper is to (a) propose exploration of several potential malleable factors related to burnout of special educators serving students with and at risk for emotional and behavioral disorders, (b) li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(61 citation statements)
references
References 114 publications
1
60
0
Order By: Relevance
“…The present study examined aspects of the first components of Garwood's (2023) model, that is, factors that precede and contribute to special education teacher burnout. Beyond burnout, the Garwood model was intended to explain factors that predicted teachers' of SWDs implementation of effective BSPs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study examined aspects of the first components of Garwood's (2023) model, that is, factors that precede and contribute to special education teacher burnout. Beyond burnout, the Garwood model was intended to explain factors that predicted teachers' of SWDs implementation of effective BSPs.…”
Section: Discussionmentioning
confidence: 99%
“…We drew upon Garwood's (2023) model to identify contextual predictors of stress and coping patterns. The data indicated that teachers in the maladaptive group were distinguished by several contextual variables.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations